2010
DOI: 10.1001/archophthalmol.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Contact Lens With Intraocular Lens Correction of Monocular Aphakia During Infancy

Abstract: Objective-To compare the visual outcomes and adverse events of contact lens to primary intraocular lens (IOL) correction of monocular aphakia during infancy.Methods-In a randomized, multicenter (12 sites) clinical trial, 114 infants with a unilateral congenital cataract were assigned to undergo cataract surgery between 1 to 6 months of age either with or without primary IOL implantation. Contact lenses were used to correct aphakia in patients who did not receive IOLs. Grating visual acuity was tested at 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 30 publications
(34 reference statements)
3
64
0
Order By: Relevance
“…It has been reported that 58 of the 114 IATS patients (50.9%) developed an adverse event (AE) in the first year following cataract surgery. 11 Among the patients with one or more adverse event, 30/48 (63%) had strabismus compared with 22/38 (58%) in the patients without an adverse event (p=0.82).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that 58 of the 114 IATS patients (50.9%) developed an adverse event (AE) in the first year following cataract surgery. 11 Among the patients with one or more adverse event, 30/48 (63%) had strabismus compared with 22/38 (58%) in the patients without an adverse event (p=0.82).…”
Section: Resultsmentioning
confidence: 91%
“…The primary outcomes at one year after cataract surgery including visual acuity, adverse events, and additional surgeries have been previously described. 11 In this report we compare the timing of onset and characteristics of strabismus between the two treatment cohorts up to one year postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…The Infant Aphakia Treatment Study was a multi-center, randomized, controlled clinical trial sponsored by the National Eye Institute to determine whether primary IOL implantation in infants younger than 7 months of age with a unilateral congenital cataract results in improved visual outcomes over contact lens correction of aphakia. 1,2 Half of the 114 infants enrolled in this multicenter study were randomized to receive an IOL with a lens power determined using the Holladay 1 formula. The mean absolute prediction error was 1.8 ± 1.3 diopters (D), with greater error noted in eyes with shorter globe axial length (AL).…”
mentioning
confidence: 99%
“…This is one of the reasons cited for considering primary IOL implantation during infancy despite the higher rate of adverse events and additional intraocular surgeries associated with IOL implantation in this age group. 3 The high success rate of contact lens wear following congenital cataract surgery in countries with socialized health care systems suggests that cost is an important factor when treating children with aphakic contact lenses. 15,18 The IATS provides further evidence that when the economic burden of contact lens use is removed from caregivers that excellent contact lens adherence can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, we recommended that infants undergoing surgery for a unilateral cataract during the first 6 months of life be left aphakic and be optically corrected with a contact lens. 3 …”
Section: Introductionmentioning
confidence: 99%